Da responsabilidade extracontratual do estado em razão de seus atos omissivos - Alcantara, Daniel Oliveira de (2012)
The aim of this study was to analyse the issue of non-contractual liability of the State for damage caused to third parties by reason of his conduct by omission, its foundations, assumptions, theories, and especially the current doctrinal differ on its, whether subjective or objective